Critical Literacies and Feminist Ethics: Mapping a Pedagogical Reform in the Preparation of Educators - Audrey M. Dentith; Jeanne F. Brady (Educational Considerations, 2004)
Those of us in university programs of education face the daunting task of preparing new and practicing teachers and school leaders with the necessary knowledge, competencies and attitudes to teach with success in the face of ever increasingly complex schooling environments.